Psychiatry: Call It Teaching or Call It Treatment - Lasch, Christopher (The Hastings Center report, 1975)
The Death of Psychiatry. By E. Fuller Torrey. Models of Madness, Models of Medicine. By Miriam Siegler and Humphry Osmond.